2011
DOI: 10.1093/ecam/nep109
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Composition and Antioxidant Capacity of Three Malian Medicinal Plant Parts

Abstract: This study evaluates the levels of total polyphenolic compounds in three Malian medicinal plants and determines their antioxidant potential. Quantitative and qualitative analysis of polyphenolics contained in plants extracts were carried out by RP-C18 RP–HPLC using UV detector. The antioxidant activity was determined by three tests. They are phosphomolybdenum, DPPH (2,2-diphenyl-1 picrylhydrazyl) and ABTS [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic)] tests. The total phenolic and the total flavonoid cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 46 publications
6
78
1
1
Order By: Relevance
“…Similarly, scavenging activities for free radicals by natural products of plant origin have been widely reported. [1,28,[45][46][47][48][49] . This study has ascertained the level of oxidative stress by estimating the concentrations of two oxidative stress indicators, namely, MDA and methaemoglobin of sickle erythrocytes incubated in aqueous extracts of three medicinal plants: Anacardium occidentale, Psidium guajava and Terminalia catappa.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, scavenging activities for free radicals by natural products of plant origin have been widely reported. [1,28,[45][46][47][48][49] . This study has ascertained the level of oxidative stress by estimating the concentrations of two oxidative stress indicators, namely, MDA and methaemoglobin of sickle erythrocytes incubated in aqueous extracts of three medicinal plants: Anacardium occidentale, Psidium guajava and Terminalia catappa.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a weak correlation was found among TFC and antioxidant capacity assays (DPPH, ferric and cupric reducing power). Similarly, some authors found weak correlation between antioxidant assays and TFC of several plant extracts (Muanda et al, 2011;Saeed et al, 2012). Principal component analysis (PCA) was also used evaluate the correlation among antioxidant capacity assays (Fig.…”
Section: Principal Component Analysis (Pca) and Correlation Analysismentioning
confidence: 99%
“…Additionally, anthocyanin amounts are largely different in the growth area of the plants, i.e. light conditions (Albert, et al, 2009), and leaves and stalks (Muanda, et al, 2009). In this study, we, therefore, obtained fresh açai fruit through a legal channel and transported it to our laboratory, preserved by dry ice.…”
Section: Extraction Of Anthocyanins and Lipophilic Ingredientsmentioning
confidence: 99%